A 350 GHz array of LEKIDs for balloon-borne CMB observations - Cacciotti, F.; Paiella, A.; Avestruz, C.; Tackur, R. Basu; Battistelli, E. S.; de Bernardis, P.; Bulbul, E.; Columbro, F.; Coppolecchia, A.; Cray, S.; D'Alessandro, G.; De Petris, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)
We present the design, optimization and laboratory characterization of an array of Lumped Element Kinetic Inductance Detectors sensitive in a frequency band centered at 350 GHz. The array consists of 313 feed-horn coupled pixels with resonant frequencies spread over 250 MHz. We present measured yield, quality factor, responsivity, quasiparticle lifetime, noise equivalent power and optical efficiency. The array is a prototype for one of the four frequency bands of OLIMPO, a balloon-borne instrument with a 2.6 m primary mirror proposed for an Antarctic flight to measure the Sunyaev–Zel’dovich effect in clusters of galaxies and their connecting filaments. Similar arrays could also be used with instruments studying the polarization of the cosmic microwave background radiation.